2003
DOI: 10.1161/01.res.0000071345.76095.07
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Vascular Smooth Muscle Cell Proliferation and Intimal Thickening After Balloon Injury by the Sulfated Oligosaccharide PI-88

Abstract: Abstract-Percutaneous transluminal coronary angioplasty is a frequently used interventional technique to reopen arteriesthat have narrowed because of atherosclerosis. Restenosis, or renarrowing of the artery shortly after angioplasty, is a major limitation to the success of the procedure and is due mainly to smooth muscle cell accumulation in the artery wall at the site of balloon injury. In the present study, we demonstrate that the antiangiogenic sulfated oligosaccharide, PI-88, inhibits primary vascular smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 33 publications
3
38
0
Order By: Relevance
“…At present, it is not clear which of these possibilities could account for this observation. It is known that FGF is abundant in the GBM (39) and that PI-88 directly binds to FGF and renders it biologically inactive (27). This known effect of PI-88 may contribute to abnormal GBM biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, it is not clear which of these possibilities could account for this observation. It is known that FGF is abundant in the GBM (39) and that PI-88 directly binds to FGF and renders it biologically inactive (27). This known effect of PI-88 may contribute to abnormal GBM biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PI-88 binds and inactivates FGF (27). Podocytes have been shown to release FGF in response to injury in PHN, and FGF administration augments podocyte injury (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flow cytometric analysis Cells were starved of glucose overnight and then incubated for 48 h in the medium containing 5 or 30 mmol/l glucose or the indicated concentrations of H 2 O 2 in the absence or presence of three HPR1 inhibitors, PI-88, heparin and sulodexide (50 μg/ml each) [28]. Cell surface heparan sulphate was stained with an anti-heparan sulphate monoclonal antibody (clone HepSS) according to previous publications [18].…”
Section: Methodsmentioning
confidence: 99%
“…A note of caution could be raised with regard to the therapeutic use of sulfated oligosaccharides in general and JG3 in particular, in that a large body of literature has documented the capability of heparin and other sulfated oligosaccharides to facilitate (as opposed to inhibit) growth factor release. Notably, in one recent study, PI-88 was also observed to enhance release of the heparan sulfate binding growth factor bFGF, and yet PI-88 inhibited bFGF-mediated cell signaling (34). However, modified heparin by glycol-splitting as N-acetylheparins failed otherwise to release bFGF from extracellular matrix and, thus, its mitogenic activity (35).…”
Section: Discussionmentioning
confidence: 99%